Maastrichtse industriëlen en het Belgische annexisme in de jaren 1918–1919 - Beaumont, Eddy de (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
Abstract: „During and immediately after the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. How did industrialists in the capital Maastricht respond to these Belgium goals? In this article, I explore the perspectives of an industrialist, a state detective and an economist in this matter. The industrialist was a fierce opponent of annexation, while the state detective was convinced that annexionists, those who were in favour of annexation, should mainly be found among major industrialists. The economist, on the other hand, did not rule out the possibility that some of Maastricht’s traders and industrialists would prefer a connection with Belgium. How did they come to these conclusions and to what extent did their considerations and other sources provide an answer to the research question of this article? Taking both gossip and facts into account, we may conclude that indeed there could have been traders and industrialists who supported the Belgian aspirations and preferred to join Belgium. However, the general claim that, in Maastricht especially, major industrialists were in favour of annexation lacks any factual evidence.“
Keywords: Annexion; Erster Weltkrieg; Industrie; Maastricht; Provinz Limburg (Niederlande); Widerstand

Op de bres voor het „Deutschtum“ in Limburg (1933–1940) - Brauer, Jan (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
„Borders engender cultural and socio-political interaction between states. Especially in border regions, issues of nationality and identity sharpen in times of political tension. As early as 1933, for instance, Limburg faced strong influence of the rising National Socialist Third Reich, partly because of the many thousands of German migrants - ‘Rijksduitsers’ - who lived and worked there. Fierce propaganda and intimidation had to activate these so-called ‘Volksgenossen’, but in addition, the Limburgers, as ‘race-Germans’, also belonged in this Reich, according to Berlin. They had strayed from Deutschtum and had to be reclaimed with the use of propaganda. This early invasive socio-political influence process – a clear prelude to the occupation years ‘40-45’ – is examined in this article from German and Dutch sources. What was the impact on the daily lives of border residents, who traditionally fostered close ties with neighbours across the border? To answer this question, this article presents new cross-border regional research in the periphery of Limburg as a contribution to the broader historiography of Dutch WWII-history.“
Keywords: Grenzgebiet; Nationalsozialismus; Provinz Limburg (Niederlande)

Grenzland im Wandel - Goertz, Willi (Heimatkalender des Kreises Heinsberg, 2019)
Keywords: Grenzgebiet; Kreis Heinsberg; Provinz Limburg (Niederlande)

Vormen van regionaal bewustzijn en nationale identiteit in Belgisch- en Nederlands-Limburg 1866–1938 - Arijs, Karen (Verloren, 2017)
„In 1839 gingen Nederland en België uit elkaar. Sindsdien waren er twee provincies met de naam Limburg en de rivier de Maas werd een staatsgrens. Karen Arijs onderzoekt of zich na het ontstaan van de beide Limburgen een grensoverschrijdend regionaal bewustzijn heeft ontwikkeld. Vonden de bewoners aan weerskanten van de Maas dat zij meer met elkaar waren verbonden dan met andere Belgen/Vlamingen respectievelijk Nederlanders/rooms-katholieken? Voelden zij zich meer verbonden met hun streek (Groot-Limburg) dan met hun land? De vraag wordt uitgewerkt aan de hand van koninklijke bezoeken, herdenkingen, historische optochten en andere openbare feestelijkheden in Hasselt, Tongeren en Maastricht. De belangrijkste conclusie van het onderzoek is dat er van interregionaal bewustzijn geen sprake was. Het grensoverschrijdend regionalisme, dat gelooft in een tijdloze toestand van 'samen horen', is een hedendaags idee.“
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2017/08/06/file_4/7325428.pdf
Keywords: Hasselt (Albertkanal); Hochschulschrift; Maastricht; Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität; Tongern

„Die Annexionsfrage steckt voller Minen“. Briefe an die Annexatie-Enquête-Commissie der Werkgemeenschap Limburg, 1945 - Haude, Rüdiger (Dies- und jenseits der Grenze. Translokale Prozesse und ihre Einwirkung auf den deutsch-niederländischen Grenzraum, 2017)
Keywords: Annexion; Grenzgebiet; Provinz Limburg (Niederlande); Selfkant

Land van heel veel grenzen. Territorialiteit en textielindustrie tussen Maas en Rijn in de achttiende en het begin van de negentiende eeuw - Knotter, Ad (Limburg. Een geschiedenis, 2015)
Keywords: Arbeitsmarkt; Provinz Limburg (Niederlande); Roermond; Textilindustrie

Over grenzen, beeldvorming en identiteit. Aspecten van Nederlandse natievorming en een problematische regionale identificatie. Limburg vanaf circa 1800 - Wessels, Leo (Limburg. Een geschiedenis, 2015)
Keywords: Grenze; Provinz Limburg (Niederlande); Regionale Identität

„Die aan ‘t verleden raakt kan altijd tooveren“. Twee standbeelden voor Hendrik van Veldeke. Lokaal initiatief en Limburgse identiteit - Arijs, Karen (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2014)
Keywords: Hasselt (Albertkanal); Kollektives Gedächtnis; Maastricht; Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität

Vervolgd in Limburg. Joden en Sinti in Nederlands-Limburg tijdens de Tweede Wereldoorlog - Roels, Leen (Verloren, 2013)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2013/07/14/file_3/5195811.pdf
Keywords: Judenverfolgung; Provinz Limburg (Niederlande); Sinti; Verfolgung

Liefde met en zonder grenzen. De geografische horizon van huwelijkspartners in Limburg in de negentiende en vroege twintigste eeuw - Ekamper, Peter; Poppel, Frank van (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Binationale Ehe; Binationales Ehepaar; Ehepaar; Kulturkontakt; Provinz Limburg (Niederlande)

Annexatie en regionale identiteit. De Annexatie-Enquête van de Werkgemeenschap Limburg in 1945 - Haude, Rüdiger (Studies over de sociaal-economische geschiedenis van Limburg. Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Annexion; Grenzgebiet; Provinz Limburg (Niederlande); Selfkant

Mijnbouw en arbeidsmarkt in Nederlands-Limburg. Herkomst, werving, mobiliteit en binding van mijnwerkers tussen 1900 en 1965 - Langeweg, Serge (Verloren, 2011)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage/2012/03/10/file_3/4423487.pdf
Keywords: Arbeitsmarkt; Hochschulschrift; Provinz Limburg (Niederlande); Steinkohlenbergbau

Last Chance. Belgium at Versailles - Tuyll, Hubert P. van (Boundaries and their meanings in the history of the Netherlands, 2009)
Keywords: Annexion; Erster Weltkrieg; Grenzgebiet; Luxemburg; Ostbelgien; Provinz Limburg (Niederlande); Seeländisch-Flandern; Versailler Vertrag (1919)

Limburg bestaat niet. Paradox van een sterke identiteit - Knotter, Ad (Bijdragen en mededelingen betreffende de geschiedenis der Nederlanden (BMGN), 2008)
Keywords: Nationalbewusstsein; Provinz Limburg (Belgien); Provinz Limburg (Niederlande); Regionale Identität

Werken over de grens. Limburgers naar Duitsland, 1870–1914 - Langeweg, Serge (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmarkt; Arbeitsmigration; Deutschland; Grenzarbeitnehmer; Provinz Limburg (Niederlande)

The incorporation of Limburg in the Dutch state - Knippenberg, Hans (Nationalising and Denationalising European Border Regions, 1800–2000. Views from Geography and History, 1999)
Keywords: Nationalbewusstsein; Provinz Limburg (Niederlande)

Bibliographie Grenzland = Bibliografie Grensland. 1981–1997 - Arbeitsgemeinschaft Grenzland = Werkgemeenschap Grensland Kreis Heinsberg - Limburg (Kreisverwaltung Heinsberg, 1998)
Aantekeningen: „Bibliografie van het materiaal dat in de genoemde periode verschenen is over het Streekgewest Westelijke Mijnstreek, de Kreis Heinsberg, het Streekgewest Oostelijk Zuid-Limburg en het Gewest Midden-Limburg.“
Keywords: Bibliografie; Grenzgebiet; Kreis Heinsberg; Landeskunde; Provinz Limburg (Niederlande)

Limburg en het Belgische annexionisme 1918–1920 - Wagemans, Karel (Studies over de Sociaal-Economische Geschiedenis van Limburg (Jaarboek Sociaal-Historisch Centrum), 1998)
Keywords: Annexion; Internationale Politik; Provinz Limburg (Niederlande); Staatsgrenze

Das Belgisch-Niederländisch-Deutsche Dreiländereck. Wechselseitige grenzüberschreitende Beziehungen und regionalgeographische Kenntnisse bei Schulkindern - Gramm, Michael (List, 1979)
Inhaltsverzeichnis: https://d-nb.info/800180437/04
Keywords: Aachen (Region); Dreiländereck; Geographieunterricht; Provinz Limburg (Belgien); Provinz Limburg (Niederlande)